Case Report: Paclitaxel-Induced Pneumonitis in Early Breast Cancer: A Single Institution Experience and Review - Ardolino, Luke; Lau, Brandon; Wilson, Isabella; Chen, Julia; Borella, Linda; Stone, Emily; Lim, Elgene (Frontiers in Oncology, 2021)
Taxane-based chemotherapy regimens are in widespread use as standard of care treatment for patients with early breast cancer, though rarely its use can be complicated by taxane-induced pneumonitis (TIP). While breast cancer is the most diagnosed cancer in women worldwide, TIP remains under-described in this setting. Key questions relate to its incidence, diagnosis and management, potential predictive biomarkers, and the balance between this life-threatening toxicity and curatively intended treatment. At a single Australian institution, 6 cases of TIP are identified among 132 patients treated with a paclitaxel-containing regimen for early breast cancer (4.55%, 95% confidence interval 1.69-9.63%). This review first outlines the presentation, management, and outcomes for these cases, then answers these questions and proposes an approach to suspected TIP in patients with breast cancer.